Ship registration law and practice - Coles, Richard M.; Watt, Edward (Lloyd's shipping law library, 2019)
Ship Registration Law and Practice is fully updated and now entering its third edition. Part of Lloyd's Shipping Law Library, it is the most authoritative guide to the theory and practice of ship registration in the most popular jurisdictions. It contains the reference material needed to submit a vessel for registration at the leading ship registries world-wide, as well as extracts from key international conventions in this area, a new statistical analysis of the world merchant fleet and Port State control rankings.